Differential modes of engagement in the Internet era: a latent class analysis of citizen participation and its stratification in China. Issue 2 (3rd March 2016) - Zheng, Jiawen; Pan, Zhongdang
ABSTRACT: The advent of the Internet in China has broad implications for citizen participation in public life. To assess the impact of the Internet, we need to ask questions first about the basic structural patterns of participation among Chinese population and then on whether the Internet may provide new opportunities for disengaged people, or expand the scope of participation, or reinforce the existing structural conditions that hamper citizen participation. We address these questions with data from a nationally representative sample survey in China. Through a latent class analysis, we differentiate four types of participation. We conduct a multinomial analysis to show that the Internet recruits some disengaged, but capable participants into public life, but overall, it allots more opportunities for the socioeconomically advantaged segments of the population.